The effect of silver nitrate on the excitability of some secondary metabolite compounds of Melia azedarach L. ex vivo. (Journal of the College of Basic Education, 2022)
The current research was conducted in the Plant Tissue Culture Laboratory, Department of Life Sciences, College of Science, Al-Mustansiriya University, with the aim of increasing the production of some secondary metabolite compounds in tissue cultures of Melia azedarach L. using silver nitrate (AgNO3) as an abiotic elicitor and comparing its productivity with that of the whole plant. The leaves were sterilized using sodium hypochlorite at a concentration of 1% for 5 minutes. Callus was induced by culturing young leaves separated from the plant on MS nutrient medium supplemented with 2,4-Dichlorophenoxy acetic acid (2,4-D) at a concentration of 1.0 mg/L. The same medium above was used to maintain the induced callus. The compounds of secondary metabolites were estimated by quantitative and qualitative analysis